Intoxication With Endogenous Angiotensin II: A COVID-19 Hypothesis - Sfera, Adonis; Osorio, Carolina; Jafri, Nyla; Diaz, Eddie Lee; Campo Maldonado, Jose E. (Frontiers in Immunology, 2020)
The severe acute respiratory syndrome coronavirus 2 has spread rapidly around the globe, however despite its high pathogenicity and transmissibility, the disease severity varies widely. While the prognosis is favorable in most patients, critical illness, manifested by respiratory distress, thromboembolism, shock, and multiorgan failure, has been reported in about 5% of cases. Several studies have associated poor COVID-19 outcomes with the exhaustion of natural killer cells and cytotoxic T cells, lymphopenia and elevated serum levels of D-dimer. In this article, we propose a common pathophysiological denominator for these negative prognostic markers, endogenous angiotensin II toxicity. We hypothesize that, like in avian influenza, COVID-19 outlook is negatively corelated with the intracellular accumulation of angiotensin II promoted by the viral blockade of its degrading enzyme receptors. In this model, upregulated angiotensin II causes premature vascular senescence, leading to dysfunctional coagulation and immunity. We hypothesize further that angiotensin II blockers and immune checkpoint inhibitors may be salutary for COVID-19 patients with critical illness by reversing both the clotting and immune defects.